Training for COVID-19 vaccination educator to counter vaccination misinformation in 10 cities in Indonesia: Training for COVID-19 Vaccination Educator - Ekorini Listiowati; Agus Samsudin; Mochamad Iqbal Nurmansyah; Husnan Nurjuman; Yuanita Wulandari; Waode Asmawati; Dirwan Suryo Soularto (Universitas Muhammadiyah Malang, 2023)
The COVID-19 pandemic in Indonesia has resulted in high morbidity and mortality from COVID-19. Providing COVID-19 vaccination is one step to minimize the impact of COVID-19. However, the interest of the people in Eastern Indonesia to get the COVID-19 vaccine is still low. This is due to misinformation regarding the impact of the COVID-19 vaccine and the need to mobilize outside the region. This community service aims to produce COVID-19 vaccine educators so they can properly educate the citizens regarding the COVID-19 vaccine. This Community Service is carried out in the form of COVID-19 vaccine educator training using pre-posttest score assessment and roleplay. Information and educational communication media in the form of flipcharts and auxiliary cards. The training was held for 8 hours in 1 day in Manado, North Sulawesi. 61 participants consisting of COVID-19 volunteers, religious leaders and community leaders have attended the training. Most participants showed an increased understanding of the COVID-19 vaccine and were able to roleplay in conducting COVID-19 vaccine education using flipcharts and aid cards.